Hematological and cytogenetic effects in the offspring of laboratory rats exposed to incorporated 131I - О. B. Ganzha; N. M. Riabchenko; А. І. Lypska; N. К. Rodionova; V. V. Talko (Ядерна фізика та енергетика)
Investigations of peripheral blood counts and bone marrow cytogenetic parameters of laboratory white male rats, descendants of the animals treated with incorporated 131I, were carried out. According to the established experimental model, sodium iodide was administered to male and female rats (parents of the first generation offspring) with the activity of 27.35 kBq per animal. Patterns and features of alterations in the hematopoietic system found in the rat first generation offspring are discussed.